Occupational-Related Injuries and Associated Risk Factors Among Healthcare Workers Working in Developing Countries: A Systematic Review - Desi Debelu; Dechasa Adare Mengistu; Sina Temesgen Tolera; Alemayehu Aschalew; Wegene Deriba (SAGE Publishing, 2023)
Background Occupational-related diseases or illnesses account for an estimated 2.4 million deaths worldwide every year. Currently, occupational hazards threaten healthcare workers' (HCWs) lives, safety, and well-being. Therefore, providing the prevalence and major causes of occupational-related diseases may enable injury reduction and the creation of safer working environments, which are important for providing higher quality services. The current study aimed to determine the prevalence of occupational-related injuries and associated risk factors among HCWs, particularly in developing countries. Methods The articles published in English were retrieved using a combination of Boolean logic operators (AND, OR, and NOT), Medical Subject Headings (MeSH), and keywords in electronic databases (SCOPUS/Science Direct, Web of Science, DOAJ, PubMed/MEDLINE, CINAHL, and Google Scholars). Using Joanna Briggs Institute critical appraisal tools, a quality assessment was conducted to determine the articles' relevance. In addition, the relevant articles were identified through a series of assessment and evaluation stages. Results About 721 studies were searched using electronic databases, of which 36 articles included 139,578 HCWs. The average prevalence of occupational-related injuries among HCWs in the career and previous last year accounted for 60.17%, ranged from 32% to 87.8% and 39.16%, ranged from 1.14% to 87%, respectively. The current study found that sex and hours worked, stress at work, occupation, age, training in infection prevention, use of universal precautions, recapping needles, ward work experience, staffing and resource adequacy, awareness, outdated guidelines, and previous exposure to sharp injury were statistically associated with occupational-related injuries. Conclusions This study revealed that 39% and 60% of HCWs experienced occupational-related injuries in the last year and during their career, respectively. Therefore, the appropriate measures must be taken to reduce the burden of occupational-related injuries by following standard precautions or occupational health and safety measures.